SecM-Stalled Ribosomes Adopt an Altered Geometry at the Peptidyl Transferase Center - Bhushan, Shashi; Hoffmann, Thomas; Seidelt, Birgit; Frauenfeld, Jens; Mielke, Thorsten; Berninghausen, Otto; Wilson, Daniel N.; Beckmann, Roland (PLOS Biology, 2011)
A structure of a ribosome stalled during translation of the SecM peptide provides insight into the mechanism by which the large subunit active site is inactivated.